2016
DOI: 10.1016/j.matdes.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of a material for rapid colorimetric Fe2+ detection

Abstract: Wereport on the rational design of a novel TiO2 based screen-printed material suitable for sensitive and selective\ud detection of iron ions in water. This includes the synthesis and characterization of large mesoporous TiO2 nanostructures,\ud screen-printing of thick titania films on glass surfaces and their functionalization with 2,2′:6′,2″-\ud terpyridin-4′-ylphosphonic acid (terpy). The ultra-high affinity between iron ions and the TiO2-anchored terpy\ud receptor makes this system potentially applicable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The general conductive ink is a metal-filled paste with a solid content of a certain percentage, for which the curing process under a required temperature by the screen machine is necessarily performed after the ink is pressed. Although the screen printing technique was invented in ancient China, this technique has been systematically developed in the last 20 years and is employed for the design of robust non-bendable chemical sensors [ 28 ], electrochromic materials [ 29 ], and non-bendable UHF-RFIDs [ 30 ]. However, the invention of conductive compositions for textile printing, described by Ujiie in 2006 [ 31 ] that was further developed by Cie in 2015 [ 32 ] opens the door for utilization of screen printing in flexible electronics.…”
Section: Fundamentals Of Textile Uhf-rfid Sensor Techniquesmentioning
confidence: 99%
“…The general conductive ink is a metal-filled paste with a solid content of a certain percentage, for which the curing process under a required temperature by the screen machine is necessarily performed after the ink is pressed. Although the screen printing technique was invented in ancient China, this technique has been systematically developed in the last 20 years and is employed for the design of robust non-bendable chemical sensors [ 28 ], electrochromic materials [ 29 ], and non-bendable UHF-RFIDs [ 30 ]. However, the invention of conductive compositions for textile printing, described by Ujiie in 2006 [ 31 ] that was further developed by Cie in 2015 [ 32 ] opens the door for utilization of screen printing in flexible electronics.…”
Section: Fundamentals Of Textile Uhf-rfid Sensor Techniquesmentioning
confidence: 99%
“…Previously, it was demonstrated that 2,2':6',2''terpyridine (terpy) moiety can form stable complexes with a variety of metals in different oxidation states. [17][18] This moiety as a part of different ligands can be used to covalently anchor and grow electrochromic (EC) molecular wires on a flat surface [19][20] or to form EC coatings or separate nanosheets of metallo-supramolecular polymers. [21][22][23] Our group has developed ECDs that utilize just a monolayer of EC terpy-based metal complexes deposited on enhanced surface area conductive supports [24] to form the working electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Among the others, ECDs based on polypyridine metal‐coordination complexes demonstrate enhanced cyclic stability, short switching times and exceptional coloration efficiency. Previously, it was demonstrated that 2,2′:6′,2′′‐terpyridine (terpy) moiety can form stable complexes with a variety of metals in different oxidation states [17–18] . This moiety as a part of different ligands can be used to covalently anchor and grow electrochromic (EC) molecular wires on a flat surface [19–20] or to form EC coatings or separate nanosheets of metallo‐supramolecular polymers [21–23] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the concentration of iron in seawater is relatively low, it is a challenge to accurately measure the iron content during environmental analysis. Fe(II) can be detected by many methods such as spectrophotometry [9][10][11], fluorescence [12,13], phosphorescence [14], etc. Although these methods have serious of advantages, they are usually inconvenient, expensive, and time-consuming [15].…”
Section: Introductionmentioning
confidence: 99%